Heating, piping, and air conditioning. (Domestic Engineering Co., 1929)
Vols. for May 1929-Dec. 1958 include the Journal of the American Society of Heating and Air-Conditioning Engineers (called in 1929-54 American Society of Heating and Ventilating Engineers) in "Journal section."